2020
DOI: 10.1097/phm.0000000000001464
|View full text |Cite
|
Sign up to set email alerts
|

Which Ultrasound Parameter Is More Accurate in the Diagnosis of Carpal Tunnel Syndrome

Abstract: Objective The aim of this study was to compare the accuracy of cross-sectional area (CSA), resistive index (RI), and strain ratio (SR) in carpal tunnel syndrome (CTS). Design This prospective and case-control study included patients with a diagnosis of CTS and a healthy control group. The participants were examined with an ultrasound Doppler system equipped with a high-resolution (5–18 MHz) linear probe (Philips L18-5). CSA, RI, and SR values were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The diagnostic tests evaluated and their weighted mean sensitivity and specificity are outlined in Tables 2 and 3. 16-128 Although studies utilizing “clinical diagnosis” as a reference standard were treated as a unified subset, many studies 16-128 were found to utilize different definitions of clinical diagnosis. An outline of the utilized definitions for “clinical diagnosis” is presented in Supplemental Digital Content 1.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic tests evaluated and their weighted mean sensitivity and specificity are outlined in Tables 2 and 3. 16-128 Although studies utilizing “clinical diagnosis” as a reference standard were treated as a unified subset, many studies 16-128 were found to utilize different definitions of clinical diagnosis. An outline of the utilized definitions for “clinical diagnosis” is presented in Supplemental Digital Content 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, those studies with a positive correlation with EDX severity noted that the ability of ultrasound to differentiate between the moderate and severe groups was poor 17,24 . A recent study by Ciloglu et al found that CSA was able to differentiate between the mild/moderate and severe groups of the Padua EDX protocol using a cutoff of 15 cm 2 ; however, they had a fairly low sample size of only 36 wrists 15 . In our study, ∆CSA had poor concordance with both CSI severity categories and Bland severity grading.…”
Section: Discussionmentioning
confidence: 98%
“…Roll and colleagues concluded that the lack of standardized methodology has made it difficult to determine the diagnostic utility of ultrasound in CTS evaluation 13 . Additionally, the current literature is conflicting on whether ultrasound parameters can be used to determine CTS severity grading, 12,14‐17 which limits utility of ultrasound diagnostics because severity grading may be used to predict surgical outcome and guide treatment 6,7,18,19 . This indicates that further studies are necessary to characterize the diagnostic accuracy of the ultrasound measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] These reference values have been based on either healthy control subjects (i.e., normal values), providing the 95% confidence interval of a nerve CSA for a given population, or on diagnostic studies in patients and controls using a receiver operating curve analysis for optimal sensitivity and specificity in specific disorders (i.e., disease specific cut-offs), such as carpal tunnel syndrome (CTS). 12,13 Normal values provide a sensitive means of detecting nerve pathology, but they are nonspecific, whereas disease-specific cut-offs have a known, deliberately chosen, specificity. However, diseasespecific reference values are only validated for use in patients having (only) that particular disease from which the values were derived.…”
Section: Various Sets Of Reference Values Have Been Published For Manymentioning
confidence: 99%
“…Various sets of reference values have been published for many nerves in different populations to help detect the presence of possible abnormalities 9–11 . These reference values have been based on either healthy control subjects (i.e., normal values), providing the 95% confidence interval of a nerve CSA for a given population, or on diagnostic studies in patients and controls using a receiver operating curve analysis for optimal sensitivity and specificity in specific disorders (i.e., disease specific cut‐offs), such as carpal tunnel syndrome (CTS) 12,13 . Normal values provide a sensitive means of detecting nerve pathology, but they are nonspecific, whereas disease‐specific cut‐offs have a known, deliberately chosen, specificity.…”
mentioning
confidence: 99%